Sphingomonas Infections Arising from Hospital Plumbing Fixtures. (4th October 2017) - Zellmer, Caroline J; Michelin, Angela V; Johnson, Ryan C; Dekker, John P; Frank, Karen M; Henderson, David K; Lau, Anna F; Segre, Julia A; Palmore, Tara N
Abstract: Background: Following a rise in nosocomial infections due to Sphingomonas, a waterborne Gram-negative organism, we undertook an epidemiological investigation to identify possible sources and develop a remediation strategy. Methods: We analyzed Sphingomonas isolates from 30 inpatients in the past 11 years, and we reviewed each patient's chart. We collected swabs of faucets, water samples, and free and total chlorine levels from rooms of Sphingomonas patients from 2016, using unrelated rooms as controls. Water samples and chlorine levels were collected from hospital pipes. Swabs were placed into 1 mL TSB and cultured to sheep blood agar. Isolates were identified by MALDI-TOF MS. Water samples were tested via membrane filtration (500 mL) and spread plate method (1 mL). Patient and environmental Sphingomonas isolates underwent whole genome sequencing, and were analyzed with Mash and Snippy for overall genomic sequence and single-nucleotide polymorphisms comparisons, respectively, to assess relatedness. Results: Of 27 faucets examined, 59% grew Sphingomonas spp., and 33% grew highly-resistant S. koreensis . Of 21 water samples, 76% grew Sphingomonas spp., and 48% grew S. koreensis. Sequence analysis demonstrated strong genetic similarity among S. koreensis clinical isolates from the past 11 years and recent faucet and water isolates. One patient's S. koreensis isolate was genetically related to isolates from faucets in his room. Sphingomonas did not grow from samples collected from municipal water or some of the far upstream water pipes within the hospital. Free chlorine levels were extremely low in hot water, leading to a program of flushing in order to restore and maintain adequate levels. Among 7 contaminated faucets that were replaced, 3 became recolonized within 4 weeks, and continued to grow Sphingomonas from water. Conclusion: Investigation and genome sequencing suggest long-standing S. koreensis colonization within the hospital plumbing system that has served as a reservoir for sporadic infections among immunosuppressed patients. Remediation of Sphingomonas plumbing contamination is an ongoing challenge guided by few published data. Hospital water must be rendered safe for even the most immunosuppressed patients. Disclosures: All authors: No reported disclosures.